Consumer Consideration in Purchase Decision of Specs Sports Shoes Product through Brand Image, Product Design and Price Perception - Sri Widyastuti; Muhammad Said (International Journal of Supply Chain Management, 2017)
The SPECS sport shoes create the slogan Buktikan Indonesiamu (Prove your Indonesia) is the original product from Indonesia. The product assumed unable attract the Indonesian people to wear it. It may be possible because the purchase decision of shopping good like SPECS sport shoes is not an immediate decision due to the comparison of price, product design, and quality product that give positive brand image in a consumers mind. This study aim to analize the influence of brand image, product design, and price perception toward the purchase decision f SPECS sport shoes. Unit analysis of this study is 100 collage students whose wear SPECS shoes. Data analysis technique in this study is descriptive and verificative analysis with double regression analysis. The finding shows that brand image, product design, and price perception of SPECS sports shoes have the influence to purchase decision. If the brand image is formed, it will push the purchase decision. Design product have a role to help consumer acquired the expected benefit of the product. Price have the influence to purchase decision if the consumer acceptance of price perception is getting better.